[Rezension von: Calvo-Quiros, William A., Undocumented saints : the politics of migrating devotions] - Nabhan-Warren, Kristy ca. 20./21. Jh. (A journal of church and state, 2025)
William A. Calvos-Quirós’s Undocumented Saints is a deeply researched and stunningly written book about Latinx popular Catholic saints. His debut book care